2011
DOI: 10.1002/clen.201100257
|View full text |Cite
|
Sign up to set email alerts
|

Mineral Content of Bottled and Desalinated Household Drinking Water in Kuwait

Abstract: Three hundred and twenty-two samples of desalinated household water were collected from 99 sampling locations that covered 95% of Kuwaiti's residential areas. Seventy-one brands of bottled water were collected from Kuwaiti markets. The water quality parameters that were studied included pH, electrical conductivity (EC), total dissolved solids (TDS), F À , Cl . The analysis yielded a large range of results for most of these parameters, with differences in some cases exceeding 10-fold. With a few exceptions, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 70 publications
0
12
0
Order By: Relevance
“…Furthermore, numerous studies on the TE content of BW have indicated the high possibility of severe water contamination as a result of leaching from the storage bottles [49][50][51][52][53][54]. By contrast, the levels of TEs in the desalinated HW at the consumer point are mainly influenced, as for previously studied parameters [34,36,40,42], by the operational processes that are used at the desalination plants, the nature of the intake seawater, the plant's position on the coast of Kuwait, the nature and type of distribution network, the type of household storage, and the piping and plumbing facilities. It is also important to note that the sole source of HW was distilled water that was blended with brackish water.…”
Section: Resultsmentioning
confidence: 95%
See 2 more Smart Citations
“…Furthermore, numerous studies on the TE content of BW have indicated the high possibility of severe water contamination as a result of leaching from the storage bottles [49][50][51][52][53][54]. By contrast, the levels of TEs in the desalinated HW at the consumer point are mainly influenced, as for previously studied parameters [34,36,40,42], by the operational processes that are used at the desalination plants, the nature of the intake seawater, the plant's position on the coast of Kuwait, the nature and type of distribution network, the type of household storage, and the piping and plumbing facilities. It is also important to note that the sole source of HW was distilled water that was blended with brackish water.…”
Section: Resultsmentioning
confidence: 95%
“…The analyzed TEs in this study were Al, As, B, Ba, Be, Cd, Cr, Co, Cu, Fe, Pb, Mn, Hg, Mo, Ni, Sb, Se, Sr, Ti, V, and Zn. The levels of the macronutrients Ca, Mg, K, and Na and other water quality parameters of the samples collected in this study (either HW samples or BW brands) have been presented and discussed previously [42]. Table 1 shows the summary of the statistics of the studied TEs of the BW and their DL along with the WHO guideline values (WHO-GV) [55], the US-EPA maximum contaminant levels (US-EPA-MCL) [56] and the European Community-parametric values (EC-PV) [57].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…(K), antimony (Sb), selenium (Se), sodium (Na), strontium (Sr), titanium (Ti), vanadium (V), and zinc (Zn), were measured according to US-EPA Method 200.8 [35] with an Agilent ICP/MS 7500ce (Agilent, Palo Alto, CA, USA) that was equipped with an octopole reaction system, a micromist nebulizer, a bonnet and shield, and an integrated autosampler. Details regarding the analytical procedures, quality control (QC), quality assurance (QA), and detection limits (DLs) have been reported elsewhere [15,16].…”
Section: Determination Of Analyte Concentrationsmentioning
confidence: 99%
“…A literature survey indicated that numerous studies have been performed worldwide to evaluate the TEs in drinking water produced from ground or surface water [4,[6][7][8][9] or through the thermal desalination of seawater [10][11][12][13][14]. Desalinated household drinking water (HW) in Kuwait has been extensively studied to evaluate the levels of TEs [12,15], minerals [16], disinfection byproducts (DBPs) known as haloacetic acids [17,18] and halomethanes [19,[21][22][23], and organic contaminants [24]. Moreover, Al-Fraij et al reviewed the various sources of contamination of drinking water in Kuwait during the transportation to consumers [25] and concluded that the monitoring process is inadequate.…”
Section: Introductionmentioning
confidence: 99%